Neural Plasticity in Functional and Anatomical MRI Studies of Children with Tourette Syndrome - Heike Eichele; Kerstin J. Plessen (Behavioural Neurology)
Background: Tourette syndrome (TS) is a neuropsychiatric disorder with childhood onset characterized by chronic motor and vocal tics. The typical clinical course of an attenuation of symptoms during adolescence in parallel with the emerging self-regulatory control during development suggests that plastic processes may play an important role in the development of tic symptoms.